PENGARUH PENDIDIKAN AGAMA ISLAM TERHADAP AKHLAK PESERTA DIDIK DI SMP ISLAM ULUWWUL HIMMAH - Sultan, Atika Khairunnisa; Robie Farenza (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
Uluwwul Himmah Medan Middle School is an Islamic educational institution which is expected to produce future generations of Muslims who adhere to Islamic law in accordance with the Al-Qur’an and As-Sunnah, and therefore a learning process must be built in the classroom and outside the classroom that is can help students’ good morals. The influence of Islamic religious education in the formation of students’ morals can be seen from the material presented in the form of religion which is obtained from aqidah, laws in daily worship which are obtained from fiqh, guidelines for behavior obtained from moral education, so this research aims to find out how much The great influence of Islamic religious education studied at school has on the morals of students at Uluwwul Himmah Middle School Medan and to find out what efforts the school has made to improve the morals of students at Uluwwul Himmah Middle School Medan. This research method uses a qualitative descriptive method by means of a case study. The results of this research are that there has been a change in the morals of students at Uluwwul Himmah Middle School, Medan.